2022
DOI: 10.21037/atm-22-542
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of NEAT1/PINK1-mediated mitophagy in chronic obstructive pulmonary disease induced by cigarette smoke or PM2.5

Abstract: Background: This study sought to explore the underlying mechanism of long non-coding ribonucleic acid nuclear enriched abundant transcript 1 (NEAT1) and PTEN-induced kinase 1 (PINK1)-mediated mitophagy in chronic obstructive pulmonary disease (COPD) induced by cigarette smoke (CS) or fine particular matter (PM 2.5 ). Methods:In total, 30 male Wistar Rats were divided into the following 3 groups: (I) the COPD group exposed to CS (CSM); (II) the COPD group exposed to PM 2.5 (PMM); and (III) the control (Ctrl) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…This is supported by our data. Our pathway analysis also corroborates prior literature on the possible role of mitochondrial autophagy (mitophagy) in emphysema (65, 66). The canonical WNT signaling pathway, which maintains tissue homeostasis and regulates cell differentiation and apoptosis (67), is a known activator of mitochondrial biogenesis (68).…”
Section: Discussionsupporting
confidence: 89%
“…This is supported by our data. Our pathway analysis also corroborates prior literature on the possible role of mitochondrial autophagy (mitophagy) in emphysema (65, 66). The canonical WNT signaling pathway, which maintains tissue homeostasis and regulates cell differentiation and apoptosis (67), is a known activator of mitochondrial biogenesis (68).…”
Section: Discussionsupporting
confidence: 89%
“…Hence, we advise that up-regulated lncRNAs should be a better choice for diagnosis accuracy. NEAT1 is a lncRNA found to be expressed widely in a variety of mammalian cell types and involved in the occurrence and development of a variety of diseases [ 47 , 48 ]. Ming et al found high expression of NEAT1 in AECOPD and COPD patients; the increased expression of NEAT1 may be associated with the stage of COPD and positively correlated with GOLD grade [ 13 , 15 ], and the underlining mechanisms were considered to regulate inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated and chronic exposure to PM 2.5 causes reduced mitochondrial fusion and impaired dynamics with the reduction of optic atrophy 1 (OPA1) and mitofusin2 (MFN2) PM 2.5 causes mitochondrial morphology damage with mitochondrial swelling, vacuole formation, and crystal destruction [27]. In addition, in damaged mitochondria, PTEN-induced kinase 1 (PINK1), a mitophagy regulatory protein, accumulates in the mitochondrial outer membrane, thereby inducing an abnormal mitophagy process resulting in a decrease in mitochondrial volume, inhibition of mitochondrial respiratory function, and an increase in mitochondrial ROS levels [28]. This mitochondrial deficit induces abnormal energy metabolism in lung tissues by reducing the MMP level and damaging the sodium-potassium pump and calcium pump [26].…”
Section: Discussionmentioning
confidence: 99%